Analisis Kesulitan Belajar Siswa Kelas XI pada Mata Pelajaran Instalasi Tenaga Listrik - Fatria Nur Fadillah; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2023)
The purpose of this study was to determine learning difficulties caused by school environmental factors experienced by class XI students in the subject of Electrical Installation at SMK Negeri 5 Padang. This type of research is a type of descriptive research with a quantitative approach method. The research instrument was a questionnaire about learning difficulties which included: teaching methods, teacher-student relations, student-student relations, school discipline, and school facilities. This questionnaire has been validated by expert lecturers from the Department of Electrical Engineering before being tested and distributed to respondents. The subjects of this study were students of class XI in the subject of Electrical Installation with a total of 30 respondents. The data analysis used is quantitative descriptive to get the average score, the middle score, the score that appears most frequently, the total score/value, the minimum score, the maximum score, and the standard deviation. The results showed that the school environmental factors that caused the most dominant learning difficulties were the teacher-student relationship and school facilities. Teachers who are not authoritative in the learning process cause students not to care about what the teacher explains. Inadequate school facilities such as practicum tools, cause delays in the student learning process in practice so that students experience learning difficulties. It can be suggested that teachers are expected to use effective teaching methods in accordance with technological developments. Students must increase self-awareness of the need for learning and motivate them to get maximum learning results. The school completes the existing facilities in the school to facilitate the learning process.